Moderate Rainfall and High Humidity During the Monsoon Season, Negligence in Using Malaria Protection Methods and High Proportion of Mild Symptomatic Patients Were the Driving Forces for Upsurge of Malaria Cases in 2018 Among Tea Tribe Populations in Endemic Dolonibasti Health Sub-center, Udalguri District, Assam State, North-East India - Ahmed, Rahim Ali; Shankar, Hari; Hussain, Syed Shah Areeb; Swargiary, Ananta; Kumar, Avdhesh; Tarique, Mohammad; Prabhakar, Pankaj; Suri, Harpal Singh; Singh, Kuldeep; Chakma, Joy Kumar; Singh, Jyoti; Begum, Afluza (Frontiers in Medicine, 2022)
Malaria elimination is a global priority, which India has also adopted as a target. Despite the malaria control efforts like long-lasting insecticidal nets distribution, rounds of indoor residual spray, the introduction of bi-valent rapid diagnostic tests and artemisinin combination therapy, malaria remained consistent in Dolonibasti sub-centre of Orang block primary health centre (BPHC) under the district Udalguri, Assam state followed by abrupt rise in cases in 2018. Therefore, we aimed to investigate the factors driving the malaria transmission in the outbreak area of Dolonibasti sub-centre. Malaria epidemiological data (2008-2018) of Udalguri district and Orang BPHC was collected. The annual (2011-2018) and monthly (2013-2018) malaria and meteorological data of Dolonibasti sub-centre was collected. An entomological survey, Knowledge, Attitude and Practices study among malaria cases (n=120) from Dolonibasti was conducted. In 2018, 26.1 % (2136/ 8188) of the population of Dolonibasti were found to be malaria positive, of which 55% were adults (n=1176). Majority of cases were from tea tribe populations (90%), either asymptomatic or with fever only, 67.5 % (81/120) had experienced malaria infection during past years. The outbreak was characterized by a strong increase in cases in June 2018, high proportion of slide falciparum rate of 26.1% (other years average, 15.8%) and high proportion of P. falciparum of 81.2 % (other years average, 84.3%). Anopheles minimus s.l. was the major vector with 28.6% positivity and high larval density in paddy fields/ drainage area. Annual relative humidity was associated with rise in malaria cases, annual parasite incidence (rs=0.69, 90%CI; p=0.06) and slide positivity rate (rs=0.83, 95%CI; p=0.01). Older people were less educated (rs=-0.66; p<0.001), had lesser knowledge about malaria cause (rs=-0.42; χ2=21.80; p<0.001) and prevention (rs=-0.18; p=0.04). Malaria control practices were followed by those having knowledge about cause of malaria (rs=0.36; χ2=13.50; p<0.001) and prevention (rs=0.40; χ2=17.71; p<0.001). Altogether, 84.6% (44/52) of the respondents did not use protective measures. We described a sudden increase in malaria incidence in a rural, predominantly tea tribe population group with high illiteracy rate and ignorance on protective measures against malaria. More efforts that are concerted needed to educate the community about malaria control practices.